Models of Evaluating Curriculum for Language Education in Higher Education - Paudel, Pitambar (AWADHARANA, 2022)
Any curriculum has to be updated with the changing needs and aspirations of the society. Its regular and systematic evaluation helps to show its role and effectiveness in meeting the worldly needs and challenges and being changed accordingly. Considering this rationale, in this article, I tried to present various approaches or methods frequently used in curriculum evaluation process in the higher education to make curriculum updated, need based, contextual and make the learners capable of dealing with the professional, pedagogical and individual challenges they encounter with. The review of various approaches of the curriculum evaluation indicates that no single approach is universal, that is, the evaluator should select the models of evaluation as per the context, nature of curriculum and the goals of education.